The Management of E-Waste in the Public Sector: The Case of Bahrain - Marilou A. Maderazo; Aaron Paul M. Pineda (Insights into Economics and Management Vol. 11, 2021)
The researchers has conducted this study in order to analyze the preparedness of the e-waste management by the Bahrain Public Commission. The Bahrain Public Commission is a government organization which overlooks the protection of marine and environment in the Kingdom of Bahrain. All over Bahrain different colored boxes are kept for glass waste, paper waste and electronics waste. The same procedure is applied in the companies. The problem encountered is that not many people follow the waste management effectively. This may be due to lack of awareness which lead on recommendations for awareness program among the general public, hold training programs or awareness campaigns across the country. Waste Management in Developed Countries - Brought basically by their more developed industries and more advanced technology, developed nations have more efficient and standard liquid waste management plans. The E-waste management system in the Kingdom of Bahrain is in its early stage of development it needs many steps toward the EMS in the developed countries and a strong bases for legislation enforcements. It was recommended that the region may develop an e-waste management system, a national framework for the management of e-waste, like awareness, education and involve the whole community, starting pilot plans on sorting and collection of electronic wastes, including take back plans and plans for repair recycling and refurbishment, provision of a strong regulatory environment.